Endovascular Aneurysm Repair From Bench to Bed - Marty, Bettina; SpringerLink (Online service) (Darmstadt : Steinkopff, 2005)
Endovascular procedures have a tremendous impact upon modern patient care. This book summarizes covered stent-graft applications in the experimental and clinical settings. Excellent illustrations document the acute and chronic behavior of stent-grafts within the vascular system including diagnostic imaging, histologic work-up and schematic drawings. A large amount of experience on intravascular ultrasound-based repair of aortic pathologies is presented. Physicians interested in the endovascular field will find this book a very stimulating resource.
Experimental studies -- Quantification of radial pressure caused by bare and covered Wallstents -- Latex covering of Palmaz stents and its effect on stent expansion -- The healing response towards polyurethane covered Wallstents $1 (BA histological investigation -- Biological fixation of polyester vs polyurethane covered stents in a porcine model -- Animal models for endovascular graft application -- Endoleaks following endovascular repair of experimental aneurysms: Does coil embolization with angiographic $1 (Bseal$1 (Blower intraaneurysmal pressure? -- Does large oversizing of self-expandable endoprostheses compensate for aortic growth? -- Historical background -- Clinical applications -- Classification of infrarenal aortic aneurysms with respect to endovascular suitability -- Systematic and exclusive use of intravascular ultrasound for endovascular aneurysm repair $1 (BThe Lausanne experience -- Endoprosthesis and intravascular ultrasound: The tools for straightforward repair of traumatic aortic rupture -- Partial inflow occlusion facilitates accurate deployment of thoracic aortic endografts.s
Keywords: Medicine; Surgery; Medicine & Public Health; Surgery; Electronic books